2010
DOI: 10.1007/s11033-010-0336-3
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium-derived factor plays an inhibitory role in proliferation and migration of HaCaT cells

Abstract: The normal vasculature is maintained by a balance between angiogenic factors and anti-angiogenic factors. Recent studies have shown that pigment epithelium-derived factor (PEDF) can induce differentiation and inhibit angiogenesis of tumors. This study was designed to investigate the expression of PEDF and its roles in proliferation, adhesion and migration of HaCaT cells, a human keratinocyte cell line. Our results have shown that PEDF is expressed in HaCaT cells at both mRNA and protein levels determined by RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…PEDF has previously been shown to inhibit migration and proliferation in the human keratinocyte cell line HaCAT (15) and in endothelial cells (1); therefore, we wondered if PEDF would have similar effects on primary NHEK. Using a scratch wound assay on a monolayer of NHEK, cells were treated with exogenous purified recombinant human PEDF.…”
Section: Resultsmentioning
confidence: 99%
“…PEDF has previously been shown to inhibit migration and proliferation in the human keratinocyte cell line HaCAT (15) and in endothelial cells (1); therefore, we wondered if PEDF would have similar effects on primary NHEK. Using a scratch wound assay on a monolayer of NHEK, cells were treated with exogenous purified recombinant human PEDF.…”
Section: Resultsmentioning
confidence: 99%
“…However, AAPE contained pigment epithelium-derived factor (PEDF), a 50 kDa glyco-protein and a member of the serine protease inhibitor gene family. PEDF inhibits proliferation of HaCaT cells and induces S phase accumulation, and induces a significant decrease of the wound healing of HaCaT cells [42]. The close correlation between scratch wound and cell migration data suggest that PEDF can inhibit migration of HaCaT cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, plenty of data revealed that metalloproteinases are upregulated by CD9 [25,26]. JNK pathway has been implicated in MMP-9 regulation in human epidermal keratinocytes and HaCaT cells in vitro [27,28] and our previous study revealed that nullification of CD9 upegulates MMP-9 expression in mouse wound healing [14]. However, since CD9 is not only expressed in keratinocytes, but also in other types of cells in skin, it is also unclear whether the observed alteration in JNK or MMP-9 regulation in migrating epidermis in CD9 knockout wounds is directly due to the lack of CD9 in keratinocytes or indirectly due to the influences by other skin cells lacking CD9.…”
Section: Introductionmentioning
confidence: 99%